A Revolution in the Making - Hodges, Steve; Hartmann, Bjoern; Gellersen, Hans (IEEE Pervasive Computing Magazine, 2014)
We’re currently witnessing a revolution in the way pervasive computing hardware is designed, prototyped, and manufactured. A broad set of researchers and users now have access to a host of digital fabrication tools and techniques that empower them to create new devices and realize new concepts more quickly, cheaply, and easily.